Reference Values for Maximal Inspiratory Pressure: A Systematic Review - Isabela MB Sclauser Pessoa; Verônica Franco Parreira; Guilherme AF Fregonezi; A William Sheel; Frank Chung; W Darlene Reid (Canadian Respiratory Journal)
BACKGROUND: Maximal inspiratory pressure (MIP) is the most commonly used measure to evaluate inspiratory muscle strength. Normative values for MIP vary significantly among studies, which may reflect differences in participant demographics and technique of MIP measurement.